Smart Hands-Free Appliance Control During Human Absence (International Journal of Information and Electronics Engineering, 2026)
This project presents a Smart HandsFree Appliance Control During Human Absence designed for intelligent  automation of indoor appliances such as lights and fans. The system uses a Passive Infrared (PIR) motion sensor to detect activity